Financial investment constraints: A panel threshold application to German firm level data - Artur Tarassow (Hamburg University, Department Socioeconomics, 2015)
This article tests the hypothesis that financial supply-side shifts help to explain the low-investment climate of private firms in Germany. The core contention is that a firm's financial position contributes to its access to external finance on credit markets. Special emphasis is put on small and medium-sized firms as these are assumed to face more restrictive access to external sources of funds. The application of a non-linear panel threshold model allows us to group firms endogenously according to their financial position. As potential threshold variables nine different balance sheet indicators are used. The results reveal a positive relationship between cash flows and fixed capital accumulation. Additional nonlinearity suggests that financially fragile firms rely more heavily on retained earnings. In contrast to frequent assumptions, firm size does not seem to be a relevant grouping variable in general with the only exception being micro firms for which the probability to fall into a financially constrained regime is higher compared to other companies.
Older version: http://hdl.handle.net/10419/103200
Keywords: A10; C23; D24; E22; E30; G31; 330; Firm investment; Balance sheet; Financial frictions; Credit rationing; SME; Non-linear panel